(3EOGQI GdeTJQjGJ hGdeNGRf (B/s - (3Mfaj, YHO GdZaGQs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2002)
(3GdLRA GdChd(B:(3CgejI EOGQI GdehGO hGdEeOGO, JNWjW GdEMJjGLGJ ef GdehGO hEYOGO GdehGRfI GdeGdjI, GdTQGA ef GdNGQL, TQGA GdCLgRI GdQCSeGdjI, EOGQI GdeNGRf GdLRA GdKGfj(B:(3GdQbGHI Ydi GdeNRhf hJbjje GdCOGA, GdfeGPL GdJMOjOjI ddQbGHI Ydi GdeNRhf, GdfeGPL GdEMJeGdjI ddQbGHI Ydi GdeNRhf, eTGcd Gdfbd hGdJhRjY, Jbjje fTGW EOGQI GdehGO hGdEeOGOs
Keywords: (3GdTQGAs; (3GdeNGRfs